Effect of influenza vaccine on tumor necrosis factor-like weak inducer of apoptosis (TWEAK) in older adults. Issue 16 (12th April 2018) - Keshtkar-Jahromi, Maryam; Ouyang, Min; Keshtkarjahromi, Marzieh; Almed, Samah; Li, Huifen; Walston, Jeremy D.; Rios, Rebeca; Leng, Sean X.
Highlights: This pilot study showed that influenza vaccine reduces TWEAK levels in older adults. This appears to be associated with antibody responses to vaccine strains and frailty. These novel findings suggest suppression of TWEAK/Fn14 pathway as a potential mechanism. This could mediate beneficial effects of influenza vaccine against cardiovascular disease. Abstract: Influenza immunization is recommended for older adults annually, and has been reported to have cardiovascular protective effects. TNF-related weak inducer of apoptosis (TWEAK), an inflammatory mediator implicated in the development of cardiovascular diseases, could be a mechanism for such effect. The objective of this study was to evaluate the effect of influenza vaccine on TWEAK levels. Older persons over 70 years of age were recruited during 2007–2008 influenza season and immunized with the standard dose trivalent inactivated influenza vaccine. Frailty was evaluated using a validated set of criteria. Sera were collected immediately before and during the 4th week after vaccination. Pre- and post-vaccination levels of TWEAK, soluble CD163 (sCD163) and strain-specific influenza antibody titers were measured in 69 participants. Multiple regression analyses were employed to examine the effect of influenza vaccine on TWEAK and sCD163, adjusting for age, sex, and hypertension. Post-vaccination TWEAK [mean ± standard deviation (SD) = 591.7 ± 290.1 pg/ml] was significantly lower than pre-vaccination level (690.6 ± 330.0 pg/ml) (p = .003). No significant difference was observed between pre and post-vaccination sCD163 levels (p = .71). Post-vaccination TWEAK levels were significantly higher in men (p = .01) and in participants with college or higher level of education (p = .044). There was no significant difference in post-vaccination TWEAK according to other demographics or pre-existing medical conditions. A 2-fold or greater antibody titer against H1N1 vaccine strain was associated with a more pronounced reduction in TWEAK at the p < .10 level (p = .091). A time by frailty interaction term (p = .091) indicated that the vaccination-induced reduction of TWEAK was greatest among frail individuals. These results of this observational study indicate that the impact of Influenza vaccine on TWEAK, including the role of specific antibody responses of specific vaccine strains and frailty status, warrants further investigation. Such investigation may elucidate whether this effect plays a role in mediating cardiovascular protection of influenza vaccination.